Internalization of Character Values of Panji Asmarabangun and Galuh Candra Kirana In Elementary School Students - Imron, ilmawati Fahmi; Supriyono, Supriyono; Arifin, Slamet (Universitas Nusantara PGRI Kediri, 2026)
This study aims to 1) analyze the character values ​​contained in the characters of Panji Asmarabangun and Galuh Candra Kirana, 2) identify the process of internalization of the character values ​​of Panji Asmarabangun and Galuh Candra Kirana in grade 5 students of MIN 1 Kediri City 3) describe the supporting factors and obstacles to learning with teaching materials of Panji Asmarabangun and Galuh Candra Kirana folk tales. This study uses a qualitative descriptive approach with data analysis techniques of data reduction, data presentation, drawing conclusions and verification. Learning using Panji Asmarabangun and Galuh Candra Kirana folk tales has a strong impact on instilling character values ​​in grade 5 students of MIN 1 Kediri City, such as the values ​​of honesty, responsibility, courage, perseverance, loyalty, and emotional control. Support from learning with Panji Asmarabangun and Galuh Candra Kirana folk tales is using video learning media and teaching materials in the form of short novels, then the obstacle is the limited time to teach in depth and comprehensively.